Factors associated with occurrence of salmonellosis among children living in Mukuru slum, an urban informal settlement in Kenya - Mbae, Cecilia (BMC Infect Dis, 2020)
BACKGROUND: In Kenya, typhoid fever and invasive non-typhoidal salmonellosis present a huge burden of disease, especially in poor-resource settings where clean water supply and sanitation conditions are inadequate. The epidemiology of both diseases is poorly understood in terms of severity and risk factors. The aim of the study was to determine the disease burden and spatial distribution of salmonellosis, as well as socioeconomic and environmental risk factors for these infections, in a large informal settlement near the city of Nairobi, from 2013 to 2017. METHODS: Initially, a house-to-house baseline census of 150,000 population in Mukuru informal settlement was carried out and relevant socioeconomic, demographic, and healthcare utilization information was collected using structured questionnaires. Salmonella bacteria were cultured from the blood and faeces of children < 16 years of age who reported at three outpatient facilities with fever alone or fever and diarrhea. Tests of association between specific Salmonella serotypes and risk factors were conducted using Pearson Chi-Square (χ(2)) test. RESULTS: A total of 16,236 children were recruited into the study. The prevalence of bloodstream infections by Non-Typhoidal Salmonella (NTS), consisting of Salmonella Typhimurium/ Enteriditis, was 1.3%; Salmonella Typhi was 1.4%, and this was highest among children < 16 years of age. Occurrence of Salmonella Typhimurium/ Enteriditis was not significantly associated with rearing any domestic animals. Rearing chicken was significantly associated with high prevalence of S. Typhi (2.1%; p = 0.011). The proportion of children infected with Salmonella Typhimurium/ Enteriditis was significantly higher in households that used water pots as water storage containers compared to using water directly from the tap (0.6%). Use of pit latrines and open defecation were significant risk factors for S. Typhi infection (1.6%; p = 0.048). The proportion of Salmonella Typhimurium/ Enteriditis among children eating street food 4 or more times per week was higher compared to 1 to 2 times/week on average (1.1%; p = 0.032). CONCLUSION: Typhoidal and NTS are important causes of illness in children in Mukuru informal settlement, especially among children less than 16 years of age. Improving Water, Sanitation and Hygiene (WASH) including boiling water, breastfeeding, hand washing practices, and avoiding animal contact in domestic settings could contribute to reducing the risk of transmission of Salmonella disease from contaminated environments.